2002
DOI: 10.1590/s0066-782x2002001300002
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, open-label study of the efficacy and safety of telmisartan in mild to moderate hypertensive patients

Abstract: Objective -The ideal antihypertensive agent must have the following profile: it must promote effective blood pressure (BP) reduction, maintain blood pressure control over 24 hours with a single daily dose, be as effective as possible for a great number of hypertensive patients, cause no undesirable side effects have no negative effects on metabolic parameters 1 , and finally be reasonably affordable. None of the antihypertensive agents currently available have all of these characteristics. More recently, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The effectiveness of the treatment over different time durations could be explored through continuous monitoring, which was the value addition of the study as compared to manual office measurements. The overall profile of BP in both treatment groups was similar to that reported by Plavnik et al in 2002 [ 16 ]. In general, both hypertensive and normotensive individuals have similar circadian variation in BP, with higher values during the daytime and lower during the night times [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…The effectiveness of the treatment over different time durations could be explored through continuous monitoring, which was the value addition of the study as compared to manual office measurements. The overall profile of BP in both treatment groups was similar to that reported by Plavnik et al in 2002 [ 16 ]. In general, both hypertensive and normotensive individuals have similar circadian variation in BP, with higher values during the daytime and lower during the night times [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…Plavnik et al reported a mean fall to be 14.4 mmHg for SBP and 10.3 mmHg for DBP (p<0.05) after 12 weeks of Telmisartan treatment. 7 However, in this study, Telmisartan 40 mg/daily was given for 6 weeks. In those patients whose blood pressure BP levels were lower than 140/90 mmHg, the same dosage was kept for an additional period of 6 weeks.…”
Section: Effect On Blood Pressurementioning
confidence: 93%
“…6 Among the antihypertensive drugs beta blockers and diuretics (thiazides and loop diuretics) can themselves cause hyperglycemia and impair lipid profile, but ARB's and ACE inhibitors have rather shown a modest positive effect on lipid profile and insulin resistance; also both the ACE inhibitors and ARBs have been compared with a placebo for their anti-hypertensive effects but there are very few studies where they have been compared with each other so, the present study was undertaken to study the effect of ramipril and telmisartan on blood pressure and insulin resistance in hypertensive patients. 7…”
Section: Introductionmentioning
confidence: 99%